Oscillation of the rectangular thin plate on the elastic floor with two coefficients of the floor - Da, Hoang Van (Vietnam Journal of Mechanics, 1982)
In this paper the author has used asymptotic method to study the oscillatory effect of the recangular plate on the elastic floor with two coefficients. By considering the floor with two coefficients, the plate will be subjected to one of three. Following ribrestory types : the system solid or a soft matter it vibrates as a linear equation. We could choose parameters to have a necessary oscillatory kind. It is unexpected new result. we have obtained.